Técnicas de visualização de dados em gerenciamento de projetos de desenvolvimento de software : proposta de extensão do PMBOK - Couto, Júlia Mara Colleoni (2018)
Although human brain stores image more easily than text, most of the tools we use when it comes to project management are based on textual reports, such as Microsoft Office files. The number of projects that fail is still large due to several reasons, among which is the lack of understanding of the project by the stakeholders. When it comes to software development, the uncertainties, ambiguities, and complexities inherent in these projects can amplify the chances of failures. Data visualization tools and techniques can help clarify understanding of the context and project details for stakeholders, reducing the risk of project failure and facilitating communication processes. The objective of this work is to identify what is used of visual management applied to project management, in general, and by projects of various types, and verify, among the results, what can be applied in software development project management, and how it can be done. The method designed for the study is composed of 4 phases: foundation, evaluation, compilation, and proposal. Throughout the research, a systematic literature mapping was developed, followed by a survey and a focus group, resulting in the main contribution of this work: the PMBoK (PMI project management practice guide) extension proposal, containing a process, data visualization tools and techniques that can be used as support by the manager and stakeholders in a software development project.